Febre amarela em saguis-da-cara-branca (Callithrix geoffroyi) em uma paisagem urbana - Roque, Ana Thereza (2022)
The aim of this study was to investigate whether the forest areas present within a 100m buffer of the urban area influenced the events of epizootic diseases in white-headed marmosets (Callithrix geoffroyi) in the urban environment, during a yellow fever outbreak in Espírito Santo. To test the hypothesis that environmental characteristics, such as the presence and size of forest fragments near built-up areas, may affect epizootic events on the species, we performed a Poisson Regression and a Microhabitat Classification. The Poisson Regression was based on the count of epizootics in grids of 1 km² and 9 km² and the analysis of its correlation with the size of the built-up area and the forest area within each cell of the grids. Microhabitat classification was made by measuring the distance from each epizootic point to the nearest forest fragment, and by observing and categorizing the area within the 100 m buffer around each point, considering categories A, wooded urban area, and B, edge of a forest fragment. Of the 123 events analyzed, 43.90% were in areas classified as forest edge (B) and 100% of them were in forested areas. The average distance between the reporting points and the nearest forest fragment was 140 m. In Poisson Regression, the two predictor variables showed a positive correlation with the notification of epizootics. From this, we discussed a possible pattern of yellow fever transmission in urban areas that is parallel to the wild and urban ones, occurring through synanthropic vectors and involving both human hosts and non-human primates